Breeding derivatives with desirable traits using chilli (Capsicum annuum L.) stocks and popular varieties - Reddy, K P M Dhamayanthi, V R K (Journal of Spices and Aromatic Crops, 2003)
In chilli, four agronomically desirable characters viz., compact plant type, eluster fruit character, upright fruit position and destalkness were transferred from three chilli stocks using as male parent to four popular South Indian varieties using as female parent. The genes controlling the above four characters known to be monogenic and recessive in nature were transferred by selfing and screening the backcross progenies. The rate of expression of the genes responsible for the upright fruit position and clusterness were higher than the compact plant type and destalkness. Inheritance pattern of the four characters was studied to confirm the genes transferred from the chilli stocks to the popular varieties,